RICH LEVELS OF CARABIDAE BEETLE FAUNA OF NORTHWESTERN UZBEKISTAN - Eshmuratov, Adilbay Yalgashboevich (SCIENCE and SOCIETY, 2026)
The article analyzes the levels of species richness of ground beetles (Coleoptera: Carabidae) distributed in Northwestern Uzbekistan. The obtained results are important for assessing the bioecological state of the carabid fauna of Northwestern Uzbekistan and the characteristics of their distribution across different habitats.
Keywords: ground beetles; Coleoptera; Carabidae; fauna; biodiversity; species richness; population density; ecology; habitat; Northwestern Uzbekistan